the term historical novel between concept and origin - بدري, ربيعة (مجلة المخبر أبحاث في اللغة والأدب الجزائري, 2022)
This topic deals with the concept of the historical novel as a literary genre with its features and basics. Thus, it isessential to focus on the concept and its foundation which fuses two terms: novel and history in a single narrative identity. The concept of the historical novel refers to the text which recalls the events of history and reproduce them within the current time frame. The objective of doing so is to deal with the current events and therefore making a liaison between the past and the present, in which the author utilizes artistically the historical material depending on the artistic imagination and the human experience. In doing so, the author makes use of the artistic/literary devicesto produce a creative text of an aesthetic function. The concept of historical novel, with the Western and Arab writers, has gone through many phases during its evolution, which makes it a more mature, artistic and developed literary genre due to the efforts of its pioneering authors. Keywords : Novel, term, historical, employment, tools